ANALISIS PRODUK PEMBIAYAAN MULTI GUNA PADA BANK SUMUT SYARIAH KCP. LUBUK PAKAM DALAM PENERAPAN AKAD MURABAHAH - Husnul khatimah; Tuti Anggraini (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to analyze the implementation of the murabahah contract in multipurpose financing products at Bank Sumut Syariah KCP Lubuk Pakam, and to identify its compliance with sharia principles. The research method uses a qualitative approach with in-depth interviews with the bank's Operational Leader. The results showed that the implementation of the murabahah contract has been carried out with strict adherence to sharia compliance, although there are challenges in documentation and customer education. Customer perceptions are generally positive, but some complaints arise regarding the complexity of the process. The bank has made efforts to improve services through digitalization and continuous education. This study contributes to understanding and improving the implementation of murabahah contracts in accordance with sharia principles in multipurpose financing products.